Cholera Toxin Subunit B for Sensitive and Rapid Determination of Exosomes by Gel Filtration - Karolina Sapoń; Dominika Maziarz; Teresa Janas; Aleksander F. Sikorski; Tadeusz Janas (Membranes, 2020)
We developed a sensitive fluorescence-based assay for determination of exosome concentration. In our assay, Cholera toxin subunit B (CTB) conjugated to a fluorescence probe and a gel filtration technique (size-exclusion chromatography) are used. Exosomal membranes are particularly enriched in raft-forming lipids (cholesterol, sphingolipids, and saturated phospholipids) and in GM1 ganglioside. CTB binds specifically and with high affinity to exosomal GM1 ganglioside residing in rafts only, and it has long been the probe of choice for membrane rafts. The CTB-gel filtration assay allows for detection of as little as 3 × 108 isolated exosomes/mL in a standard fluorometer, which has a sensitivity comparable to other methods using advanced instrumentation. The linear quantitation range for CTB-gel filtration assay extends over one order of magnitude in exosome concentration. Using 80 nM fluorescence-labeled CTB, we quantitated 3 × 108 to 6 × 109 exosomes/mL. The assay ranges exhibited linear fluorescence increases versus exosome concentration (r2 = 0.987). The assay was verified for exosomal liposomes. The assay is easy to use, rapid, and does not require any expensive or sophisticated instrumentation.